Enhancing Children’s Motor Memory Retention Through Acute Intense Exercise: Effects of Different Exercise Durations - Angulo-Barroso, Rosa; Ferrer-Uris, Blai; Busquets, Albert (Frontiers in Psychology, 2019)
Physical exercise has been proposed as a viable means to stimulate motor learning. Exercise characteristics, including intensity and duration, may play a role in modulating the exercise effect on motor learning. While some evidence regarding the benefits of intense and relatively long exercise exists, little is known about the effect of short exercise bouts on motor learning, especially in children. This study aimed to assess the effect of long versus short intense exercise bouts on the adaptation and consolidation of a rotational visuomotor adaptation task. The participants were seventy-one healthy children from two sites divided into three groups: long exercise bout (LONG), short exercise bout (SHORT), and no exercise (CON). Children performed a rotated (clockwise 60° rotation) motor task on four different occasions: an adaptation set and 1 h, 24 h and 7 days delayed retention sets. Exercise bouts were performed prior to the adaptation set. Results showed a group effect during motor adaptation (F(2, 68)=3.160; p=0.049; η2p=0.087), but no statistical differences were found between groups. Regarding retention tests, both exercise groups (LONG and SHORT) showed superior retention compared to CON group (F(2, 68)= 7.102; p= 0.002; η2p= 0.175). No differences were found between exercise groups, indicating similar benefits for the two exercise interventions. Overall, whether the exercise duration was long or short, exercise improved motor memory retention as an estimate of memory consolidation process. The use of short exercise bouts may be suitable to improve children’s motor memory consolidation in environments where time constraints exist.